DNA methylation biomarkers in lung cancer diagnosis: closer to practical use? - Pfeifer, Gerd P.; Kernstine, Kemp H. (Translational Cancer Research, 2017)
The purpose of cancer screening is to identify those patients for whom survival might be improved by early intervention. The strategy of waiting for symptoms results in a greater proportion of patients with advanced disease, fewer treated with curative intent and even fewer surviving long term. In some patients, such as the very elderly or infirmed, lung cancer may not shorten survival, and screening in them is less likely beneficial.